KEPEMIMPINAN, KOLABORASI TIM, DAN MOTIVASI KERJA GURU: STUDI KUALITATIF PADA SD NEGERI DI KECAMATAN WALANTAKA - Asgari Asgari; Ahmad Mukhlis; Andriani Andriani (Jurnal Ilmiah Pendidikan dan Keislaman, 2025)
The quality of basic education is highly determined by teacher performance which is not only influenced by individual competence, but also by the principal's leadership dynamics, the quality of team collaboration, and work motivation. In practice, school leadership is still often administratively oriented so that it is not optimal to build a reflective professional culture. This study aims to analyze how the principal's leadership pattern shapes the dynamics of team collaboration and how the process affects the work motivation of teachers at State Elementary Schools in Walantaka District